Construção de mapas de distribuição granulométrica e batimetria do canal do Quiriri, baía de Marajó e rio Pará-PA - BATISTA, Andrey Jeferson Ferreira (2019)
The study area is on Marajó bay, located along Pará river, which receive contributions of Amazon, Tocantins and Guamá rivers. The sampling area is the Quiriri channel and Marajó bay, which have a great importance for the region, once it’s the main entry route to the regional ports, they are: Belém Port and Vila do Conde Port. It has been realized a sediment sampling at 93 spots, distributed along the Quiriri channel and the Pará River. The samples underwent the granulometric analysis, using the laser method, which analyses the distribution of the grain size. These samples has been collected with a bottom sampler, of Petersen kind, and submitted to washing for removing the salt and after was made the separation of this material to organic matter elimination and to granulometric analysis. The organic matter has been eliminated with the adding of Hydrogen Peroxide, and then submitted to laser granulometric analysis on ANALYSETTE 22/FRITSH granulometer. The given results are based on Wentworth, Shepard and Folk classifications, following the Φ (phi) scale. To the Quiriri channel, the material proved itself as being predominantly composed for the Fine Sand and Silt fractions, being present in a more significant way the sandy sediments on the central region of the channel located near the western margin, while the dots close to the east margin is composed by finer sediments, predominantly silt. On Marajó bay region, southern study area, it has been observed the fine sediments concentration in the center of the river channel and coarser sediments while getting far from the central region. Local studies reveal a more significant hydrodynamic action next to the west margin of the Marajó bay in northern study area and, consequently, a coarser granulometry in this region. Still, on southern study area it was found a place of lesser hydrodynamic activity, enabling the deposition of mud sediments. Helping the results preview, it has been created maps using an interpolation algorithm from Surfer 9.0 software, which present granulometric parameters, organic matter amount, hydrodynamic and bathymetry data spatially distributed. This work has been done through an association between Marinha do Brasil and Universidade Federal do Pará. The samples were collected aboard the L/B Denébola and after processed on Laboratório de Oceanografia Geológica e Geofísica Marinha – LIOG, institutional laboratory which aims, in a long-term, present the faciologic chart of Amazon river mouth.